Analysis of Tannin Analisis Senyawa Tanin pada Rimpang Kunyit (Curcuma longa L.) Kering dan Segar secara Spektrofotometri UV – Vis - Noviandhita, Nikita (Makassar Pharmaceutical Science Journal (MPSJ), 2025)
Turmeric is a biopharmaceutical plant originating from the Zingiberaceae family, widely distributed in Southeast Asia and Africa. The rhizome of Turmeric (Curcuma longa L.) is the most commonly used part in various applications such as traditional medicine, textile dyes, food, spices, and cosmetics. This study aims to determine the tannin content in turmeric rhizomes (Curcuma longa L.), both in dry and fresh conditions, extracted with 96% ethanol solvent, and measured using UV-Vis spectrophotometry. The results showed that the extracts of both dry and fresh turmeric rhizomes (Curcuma longa L.) contain tannin compounds. Quantitatively, the extracts were measured at a maximum wavelength of 706 nm with gallic acid as a standard, yielding the regression equation y = 0.0898x – 0.037, an r-value of 0.9955, and the average tannin content of dry turmeric rhizome extract being 29.005 mg GAE/g extract and fresh turmeric rhizome extract being 57.046 mg GAE/g extract. This study indicates that fresh turmeric rhizome extract contains higher tannin levels than dry turmeric rhizome extract.